2019
DOI: 10.1007/s42452-019-1342-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aqueous sodium silicate on properties of recycled aggregate mortar

Abstract: This study investigates the influence of sodium silicate (Na 2 SiO 3) (NS) on the strength and durability performance of recycled concrete aggregate bearing mortar (RAM). NS is used as 0%, 1%, 2%, 3%, 4%, and 5% by weight of cement in RAM. Natural aggregate mortar (NAM) serving as control mix is also produced using natural sand. Compressive strength, sorptivity coefficient, apparent porosity, chloride penetration, and mass loss due to H 2 SO 4 are investigated at various ages. Experimental results indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…The compressive strength of cement‐based composites is an important property, which is widely considered in the design of concrete structures. It can also be used to fairly estimate the other mechanical 3,12 and durability characteristics 48,50 of cement‐based materials. In this research, the compressive strength of all concrete mixtures was evaluated at the age of 28, 90, and 180 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compressive strength of cement‐based composites is an important property, which is widely considered in the design of concrete structures. It can also be used to fairly estimate the other mechanical 3,12 and durability characteristics 48,50 of cement‐based materials. In this research, the compressive strength of all concrete mixtures was evaluated at the age of 28, 90, and 180 days.…”
Section: Resultsmentioning
confidence: 99%
“…These CPs were recorded at six different locations along the edge of the failure surface. Ali 48 and Ali and Qureshi 49 have adopted similar methodologies to estimate CP. To evaluate the acid attack resistance of concrete mixes, cylindrical specimens (having height and diameter of 100 mm) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Ali [10] studied the effect of sodium silicate addition to a recycled concrete aggregate containing mortar (RAM). For this purpose, sodium silicate was used in the amounts of 0%, 1%, 2%, 3%, 4%, and 5% by weight of cement in RAM and the performance of the RAM was compared with the performance of the natural aggregate mortar (NAM).…”
Section: Sodium Silicate Solutionmentioning
confidence: 99%
“…Numerous researchers investigated the use of different approaches and methods for the improvement of concrete characteristics with RCA addition. These include removing the adhered mortar or strengthening RCA using carbonation treatment [7], mineral admixtures [8], calcium carbonate biodeposition [9], sodium silicate solution [10], and water-repellent coat by polymer treatment [11]. Several review papers are available on improving the performance of RCA.…”
Section: Introductionmentioning
confidence: 99%
“…Concrete made with RCA has been proved a weaker and expensive product than the conventional concrete [1,[11][12][13]. Impact of recycled aggregates on the economy of concrete considering performance of concrete based on strength has been broadly discussed and it was reported that higher production costs were associated with consumptions of RCA in concrete [2,3,[14][15][16]. In order to minimize the negative impact of recycled aggregates on strength and durability of concrete, Akhtar et al [1] reported that 30-50% recycled aggregates can be used in concrete with supplementary cementitious materials.…”
Section: Introductionmentioning
confidence: 99%